An analysis of ethnic relationship in Sabah based on the concept of Mikorot (Bloodbrothers) among Dusun community - Budi Anto Mohd. Tamring; Bernadette Tobi; Romzi Ationg (2020)
Many countries with various ethnicities often encountering the issue of ethnic conflicts. This issue generally linked with social relationship among members of the different ethnic groups and that this situation can be seen in Malaysia. For this reason, numbers of efforts have been made by the government to ensure that ethnic relations in Malaysia continues to be harmonious. Such efforts have been implemented through various programs, including the implementation of the Malaysian education policy. Nevertheless, the government's efforts to ensure harmonious ethnic relations are not new within the Dusun community in Sabah. This especially true following the practice of ‘mikorot’ among the Dusun community. By employing a qualitative approach, this paper explains the meanings and concepts of ‘mikorot’ in the culture of the Dusun community as well as to explain the ritual implementation of ‘mikorot’ and to understand the implications and challenges of ‘mikorot’ in the society.